Effect of Job Satisfaction in Leadership Mediation and Work Environment on Employee Performance PT. BPR Bank Daerah Bangli (Perseroda) (Local Bank in Bangli Regency) - Made Ayu Adhi Lestari; Ida Bagus Udayana Putra; Gusti Ayu Sugiati (Jurnal Ekonomi dan Bisnis Jagaditha, 2022)
This study aims to determine the effect of leadership, work environment, on employee performance with job satisfaction as an intervening variable (mediating) on the effect of job satisfaction in mediating leadership and work environment on employee performance at PT. BPR Bank Daerah Bangli (Local Bank in Bangli Regency). This research is quantitative descriptive. The sampling technique in this study used a non-probability sampling method with a saturated sample technique. By using a sample of 65 employees of PT. BPR Bank Daerah Bangli (Local Bank in Bangli Regency). The data analysis technique used is analysis using the PLS (Partial Least Square) examination method. The results showed that Leadership has a significant positive effect on employee satisfaction. The work environment has a significant positive effect on employee job satisfaction. Leadership has a significant negative effect on employee performance. This means that an increase in leadership within the company will result in a decrease in the level of employee performance. The work environment has a positive and significant effect on employee performance. Job satisfaction has a positive but not significant effect on employee performance. Job satisfaction does not mediate the influence of leadership on employee performance, Job satisfaction does not mediate the effect of the work environment on employee performance.